Problems and Strategies of The Year 8 Students at SMP Negeri 2 Pangkajene in Speaking English - Ramadhani, Fairuz Fakhirah; Korompot, Chairil Anwar; Sakkir, Geminastiti (State University of Makassar, 2025)
This research aims to find out the problems and strategies of the year 8 students at SMP Negeri 2 Pangkajene to deal with problems in speaking English. This research used a descriptive qualitative method. The subject of this research were five students of the year 8 at SMP Negeri 2 Pangkajene. The interview was used as the main instrument to collect the data. The results of this research showed that five students of the year 8 at SMP Negeri 2 Pangkajene had some speaking problems in the class which hampered them when speaking English. They are lack of confidence, limited vocabulary, peer pressure, lack of support, inhibition, feeling of having nothing to say, low or uneven participation, mother-tongue use, and lack of drive. But based of the interview results with students among those all problems, lack of confidence and lack of vocabulary are the biggest reason of their problems in speaking English. And to deal with the problems in speaking English, students employed some strategies. They are Use Paraphrase, Create New Words, Use Non-linguistic Resources, Active Participation, Vocabulary Expansion, Practice Conversation, Listening Skills, and Peer Collaboration. But based of the interview results with students among those all strategies, active participation, vocabulary expansion, and peer collaboration are commonly used by students in overcoming problems and improve their speaking skills. Keywords: Speaking, Problems in Speaking English, Students’ Strategies in Speaking English.